Proxeny and polis : institutional networks in the ancient Greek world - Mack, William (Oxford studies in ancient documents, 2015)
This volume presents a new reconstruction of proxeny, based on a detailed analysis of the function of the formulaic language of honorific decrees, and explores the way in which interstate institutions shaped the behaviour of individuals and communities in the ancient world. It draws on other material which has not been systematically exploited before to reconstruct the proxeny networks of Greek city states. The book also traces the disappearance of both proxeny and the broader institutional system of which it was part